China-Pakistan Relations: A Historical Analysis - Ghulam Ali (New York Oxford University Press, 2017)
This book examines the nature of the China-Pakistan relationship from the 1950s until April 2015, when the Chinese President Xi Jinping visited Pakistan. The author takes a historical approach and traces the growth of the alliance underpinned by domestic, regional, and international factors. The book offers a riveting account of Sino-Pakistan ties for readers with a cursory knowledge of the subject. It will also pique the interest of students, academics, and policy makers.
Includes Illustrations, Bibliography and Index.
Keywords: Diplomatic relations